2021
DOI: 10.3390/app11052001
|View full text |Cite
|
Sign up to set email alerts
|

Stenosis of Carotid Arteries and Concentration of Some Blood Lipid Parameters amongst Tobacco Smokers in Abha: A Case–Control Study

Abstract: Smoking is well known to be correlated with cardiovascular abnormalities, in particular atherosclerosis and heart diseases. This article investigates the effect and relationship of smoking tobacco on the thickness of the intima–media (IMT) belonging to the common carotid arteries (CCAs), and also blood concentration of the lipid profile (LP), mainly the total cholesterol, High Density Lipoprotein (HDL), Low Density Lipoprotein (LDL) and also triglycerides. Nineteen male tobacco smokers and thirty-five healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Byrkjeland et al [25] have demonstrated a benefcial efect of exercise training on the progression of CIMT in patients with type 2 diabetes. Regarding the efect of smoking on CIMT, our results have shown that nonsmokers were at a 73% lower chance of having thick CIM compared to smokers, this fnding is in line with the result of Alelyani et al [26] which stated that smokers exhibit a signifcant increase in the CIMT. Te contents of cigarette smoke and the abundant free radicals in, it both contribute to direct damage to the endothelium, inducing infammation and leukocyte infltration, with subsequent development of atheroma and thrombosis [27].…”
Section: Discussionsupporting
confidence: 92%
“…Byrkjeland et al [25] have demonstrated a benefcial efect of exercise training on the progression of CIMT in patients with type 2 diabetes. Regarding the efect of smoking on CIMT, our results have shown that nonsmokers were at a 73% lower chance of having thick CIM compared to smokers, this fnding is in line with the result of Alelyani et al [26] which stated that smokers exhibit a signifcant increase in the CIMT. Te contents of cigarette smoke and the abundant free radicals in, it both contribute to direct damage to the endothelium, inducing infammation and leukocyte infltration, with subsequent development of atheroma and thrombosis [27].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to most previous studies, 1,23 this study showed that smoking is associated with significantly increased IMT of the carotid arteries, possibly as a result of speeding the atherosclerotic process. However, Babiker et al noted that there is a strong association between tobacco smoking and the formation of carotid artery plaques, but he reported that the majority of the smokers did not develop narrowing and thickening of the carotid arteries.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have reported a positive relationship between smoking and the intima media thickness (IMT) of the carotid arteries, 1 while other studies have found a strong association with carotid artery plaque and alterations in carotid hemodynamics, but absence of stenosis of the carotid arteries, in some cases of smokers. 2 One study noted that the effect of smoking on the IMT depends on the gene polymorphism of the NADPH oxidase.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations